Social mobility and economic development - Guido Neidhöfer; Matías Ciaschi; Leonardo Gasparini; Joaquín Serrano (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2021)
We explore the role of social mobility as a driver of economic development. First, we map the geography of intergenerational mobility of education for 52 Latin American regions, as well as its evolution over time. Then, through a new weighting procedure that considers the participation of cohorts to the economy in each year, we estimate the impact of changes in mobility on regional economic indicators, such as income per capita, poverty, child mortality, and luminosity. Our findings show that increasing social mobility had a significant and robust effect on the development of Latin American regions.
Keywords: D63; I24; J62; O15; 330; Intergenerational Mobility; Equality of Opportunity; Development; Growth; Latin America